The 1st International Electronic Conference on Plant Science 2020
DOI: 10.3390/iecps2020-08867
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Severe Drought on Leaf Response in ABA Contrasting Tomato Genotypes (Wild Type and flacca Mutant)

Abstract: The reaction of leaf growth to drought stress is controlled by various hormones, among which ABA is one of the most important. The aim of this study was to examine the effects of ABA deficiency on tomato leaf response under severe drought stress. Therefore, ABA-mutant (flacca) and wild type (Ailsa Craig) were selected for research and in the stage of second flower truss anthesis plants were exposed to severe water deficit. The effects of severe drought on wild-type leaves and flacca mutant showed that, as a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…A decline in leaf area results in decreased water loss due to low transpiration rates and this has been shown to be a drought avoidance strategy used by plants under drought stress 5 . Other authors have shown similar correlation between severe drought stress and a reduction in leaf area 52,53,59 . Plants generally show reduction in leaf area as a strategy to adapt to drought stress.…”
Section: Discussionsupporting
confidence: 64%
“…A decline in leaf area results in decreased water loss due to low transpiration rates and this has been shown to be a drought avoidance strategy used by plants under drought stress 5 . Other authors have shown similar correlation between severe drought stress and a reduction in leaf area 52,53,59 . Plants generally show reduction in leaf area as a strategy to adapt to drought stress.…”
Section: Discussionsupporting
confidence: 64%
“…A constitutively higher ascorbate content was also observed in the Ailsa Craig cv. tomato cultivar compared to the flacca mutant [88]. On the other hand, notabilis tomato mutants in comparison to WT possess a similar ascorbate level [89], as well as abi4-insensitive Arabidopsis mutant [90].…”
Section: Drought-induced Oxidative Stressmentioning
confidence: 91%
“…Although the uncertainty ranges for the for V cmax25 regression coefficients also showed considerable overlap, the differences were greater than for the other two parameters, and the values appeared to follow climatic gradients, with higher PAR sensitivity (coefficient ) and slightly weaker auto-correlation (coefficient α) occurring at sites with greater PAR and rainfall (in increasing order of both PAR and rainfall: K67, K34, and Guy; Table 1). Varying sensitivity of traits in response to environmental change within one PFT has been reported in previous experimental studies (Anyia & Herzog, 2004;Martin-St Paul et al, 2012;Nielsen et al, 2019;Petrović et al, 2015;Ramírez et al, 2012;Yin et al, 2004). In fact, a study spanning a Mediterranean rainfall gradient found that Quercus ilex populations at the wettest site showed steeper declines in photosynthetic capacity (stomatal conductance and V cmax25 ) in response to soil water deficit than those populations at the drier sites (Martin-St Paul et al, 2012).…”
Section: Trait Variability Among Sitesmentioning
confidence: 71%